2019
DOI: 10.3390/cancers11111795
|View full text |Cite
|
Sign up to set email alerts
|

Emodin Inhibits EBV Reactivation and Represses NPC Tumorigenesis

Abstract: Nasopharyngeal carcinoma (NPC) is a unique malignancy derived from the epithelium of the nasopharynx. Despite great advances in the development of radiotherapy and chemotherapy, relapse and metastasis in NPC patients remain major causes of mortality. Evidence accumulated over recent years indicates that Epstein-Barr virus (EBV) lytic replication plays an important role in the pathogenesis of NPC and inhibition of EBV reactivation is now being considered as a goal for the therapy of EBV-associated cancers. With… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 60 publications
0
16
0
Order By: Relevance
“…Emodin has been reported to have a wide spectrum of pharmacological applications, especially hepatoprotective, anti-inflammatory, antibacterial and anti-cancer effects. Evidence shows that Emodin has a tumor-suppressor activity in many cancers ( 33 , 34 ), especially the intrinsic insensitivity of cancer cells to drugs ( 34 ). Our in vivo and vitro assays showed that Emodin suppresses the cell growth and induces apoptosis in BC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Emodin has been reported to have a wide spectrum of pharmacological applications, especially hepatoprotective, anti-inflammatory, antibacterial and anti-cancer effects. Evidence shows that Emodin has a tumor-suppressor activity in many cancers ( 33 , 34 ), especially the intrinsic insensitivity of cancer cells to drugs ( 34 ). Our in vivo and vitro assays showed that Emodin suppresses the cell growth and induces apoptosis in BC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Emodin (1, 3, 8-trihydroxy-6-methylanthraquinone) is a natural anthraquinone derivative, and is the main ingredient of many herbs including rhubarb, polygonum multiflorum , and polygonum cuspidatum ( Dong et al., 2016 ; Monisha et al., 2016 ). Pharmacological studies have shown that emodin, as a polyvalent molecule, has a variety of biological functions, such as anti-inflammatory ( Li X. et al., 2020 ; Xu et al., 2020 ), anti-bacterial ( Ji et al., 2020 ), anti-cancer ( Wu C. et al., 2019 ; Ma et al., 2020 ; Rossi et al., 2020 ) and inhibition of oxidative stress( Lee et al., 2020 ). Emodin has also been shown to have potent anti-cardiovascular activities in vitro and in vivo , including anti-inflammatory ( Wu et al., 2007 ), antioxidant damage ( Du and Ko, 2005 ), inhibition of myocardial cell fibrosis ( Evans et al., 2020 ) and other pharmacological effects.…”
Section: Introductionmentioning
confidence: 99%
“…XYQFT also contains natural compounds, including EGCG, apigenin, coumarin, genistein, and quercetin, which exhibit anti-NPC activities ( Ong et al, 2004 ; Han et al, 2010 ; Daker et al, 2012 ; Lin et al, 2014 ; Peng et al, 2018 ; Ho et al, 2019 ; Zhang et al, 2019 ). Furthermore, 1,3,8-trihydroxy-6-methylanthraquinone (emodin) from XYQFT inhibits EBV reactivation and suppresses NPC cell proliferation ( Ma et al, 2017 ; Wu et al, 2019 ). The 3-phenyl-2-propenal ( trans -cinnamaldehyde) inhibits NPC cells ( Daker et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%